Model Tests and Numerical Simulations of Liquefaction and Lateral Spreading 2019
DOI: 10.1007/978-3-030-22818-7_4
|View full text |Cite
|
Sign up to set email alerts
|

LEAP-UCD-2017 Comparison of Centrifuge Test Results

Abstract: This paper compares experimental results from every facility for LEAP-UCD-2017. The specified experiment consisted of a submerged medium-dense clean sand with a 5-degree slope subjected to 1 Hz ramped sine wave base motion in a rigid container. The ground motions and soil density were intentionally varied from experiment to experiment in hopes of defining the slope of the relational trend between response (e.g., displacement, pore pressure), intensity of shaking, and density or relative density. This paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Inverse equations from the linear regression lines were used then to determine dry density from penetration resistance. Kutter et al (2019b) showed the densities calculated from penetration resistance at 2.0 m depth were better correlated to liquefaction performance measures than densities from mass and volume.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Inverse equations from the linear regression lines were used then to determine dry density from penetration resistance. Kutter et al (2019b) showed the densities calculated from penetration resistance at 2.0 m depth were better correlated to liquefaction performance measures than densities from mass and volume.…”
Section: Discussionmentioning
confidence: 95%
“…When that point is corrected back to the trendline, the density decreases to 1602 kg/m 3 . Kutter et al (2019b) showed that at 2.0 m depth, densities determined from penetration resistances better correlate with liquefaction performance measurements than densities from mass and volume measurements. Tabulated in Table 6.2 are the reported dry densities from mass and volume and densities calculated from the linear regression and penetration resistance.…”
Section: Depth At Which the Cone Tip Touches The Surface (Depth Of Zementioning
confidence: 96%
See 1 more Smart Citation
“…The sand was deposited through pluviation in a level rigid container to achieve a range of mass densities (with a reference mean value of 1652 kg/m 3 ). The corresponding relative densities varied from about 50 to 85% (evaluated using the minimal and maximal densities reported by Kutter et al (2018Kutter et al ( , 2019, as displayed in Fig. 7.2).…”
Section: Experiments Overviewmentioning
confidence: 98%
“…ij and ΔA 2þHz ij are the two main input motion parameters that varied during the analyzed 26 LEAP centrifuge tests. The tested soil models also had variability in soil deposition and achieved grain packing (as documented by the mass densities reported by the different centrifuge facilities (Kutter et al 2018(Kutter et al , 2019). These variations have a direct effect, for instance, on stiffness properties which in turn affect the deposit response.…”
Section: Acceleration Sensitivitymentioning
confidence: 99%